2 Dimensional Hydrodynamic Flood Routing Analysis on Flood Forecasting Modelling for Kelantan River Basin - Azad W.H.; Sidek L.M.; Basri H.; Fai C.M.; Saidin S.; Hassan A.J. (EDP Sciences, 2023)
Catchments; Disasters; Display devices; Flood control; Fluid dynamics; Forecasting; Geographical regions; Hydrodynamics; Hydrology; Landforms; Moisture; Probability distributions; Rain; Soil moisture; Water levels; Watersheds; Weather forecasting; Area of responsibilities; Flood forecasting models; Hydrodynamic modelling; Hydrological modeling; Hydrological models; Probabilistic distribution; Soil moisture deficits; Spatial complexity; Floods